Comparison between an Acrylic Splint Herbst and an Acrylic Splint Miniscrew-Herbst for Mandibular Incisors Proclination Control. (19th May 2014) - Manni, Antonio; Pasini, Marco; Mazzotta, Laura; Mutinelli, Sabrina; Nuzzo, Claudio; Grassi, Felice Roberto; Cozzani, Mauro
Abstract : Aim . The aim of this study is to compare dental and skeletal effects produced by an acrylic splint Herbst with and without skeletal anchorage for correction of dental class II malocclusion. Methods . The test group was formed by 14 patients that were treated with an acrylic splint miniscrew-Herbst; miniscrews were placed between mandibular second premolars and first molars; controls also consisted of 14 subjects that were treated with an acrylic splint Herbst and no miniscrews. Cephalometric measurements before and after Herbst treatment were compared. The value of α for significance was set at 0.05. Results . All subjects from both groups were successfully treated to a bilateral Class I relationship; mean treatment time was 8, 1 months in the test group and 7.8 in the controls. Several variables did not have a statistical significant difference between the two groups. Some of the variables, instead, presented a significant difference such as incisor flaring, mandibular bone base position, and skeletal discrepancy. Conclusions . This study showed that the Herbst appliance associated to miniscrews allowed a better control of the incisor flaring with a greater mandibular skeletal effect.